Is there Afterlife: Bhavaṅga Citta going beyond Quantum Physics in the Concept of Afterlife - PHU, Ven.Vinh Phuc (The Journal of International Buddhist Studies College, 2021)
Is there afterlife? To answer this question, scientists partake in studying mind and consciousness through their experiments. In the field of Quantum Physics, Prof. Dr. Robert Lanza has introduced “Theory of Everything” namely Biocentrism, to prove that space and time are simple tools mind uses to weave information together into a coherent experience of the language in consciousness. However, Biocentrism is unable to prove that mind uses the same algorithm to create a spatio-temporal reality in dream is a real, 3-D and flesh-and-blood as the one you are experiencing now. For that, Visuddhimagga, a prominent Buddhist treatise, exceeds beyond the level of understanding in mind and consciousness that Biocentrism has reached currently. It describes how to proactively discern the underlying consciousness-layer in mind called life-continuum (Pali. bhavaṅga citta). This stream arises once the ordinary mind is in unconsciousness, such as, in sleep. In the case of death, the bhavaṅga citta turns from one form to another with its nature of continuity. Therefore, to apprehend the concept of afterlife is to study the continuity of bhavaṅga citta in the empirical experience of Quantum Physics and Visuddhimagga.